The Effect Of Particle Shape On The Filtration Rate In An Industrial Iron Ore Processing Plant - J. J. Carlson (Society for Mining, Metallurgy & Exploration, 2008)
Studies were carried out to determine whether filtration rate changes observed in an iron ore concentrator were due to variations in particle shape. It was confirmed that ores mined from different locations differed in filtration rates by as much as 60%. However, when image analysis was used to quantify the shapes of the individual particles in the filtration feed, it was found that the particle shapes showed almost no variation, and the shapes did not correlate with the filtration rate. It was also determined that the filtration rate variations were not caused by changes in particle size distribution. These results suggest that the differences in filtration rate are due to factors other than size and shape, such as surface chemistry.